EKSPLORASI PENYEBAB FUTURE ANXIETY PADA MAHASISWA TINGKAT AKHIR YANG MERANTAU - Yohana Aryyanti Hutapea; Yohanes Budiarto (STKIP Subang, 2024)
Final-year students who migrate face various challenges, such as social demands, academic pressures, and life transitions, which can trigger future anxiety. This anxiety reflects fears of uncertainty and bad possibilities in the future. This study aims to explore the factors that cause future anxiety in final year students who migrate. A mixed method approach with an exploratory sequential design was used in this study. Data were collected through an open-ended question-based qualitative survey, involving 104 final-year students who migrated (female = 90, male = 14). Based on the results of thematic analysis, it was revealed that future anxiety is mainly related to concerns about employment, including the possibility of getting a job according to interests, opportunities for growth, and compatibility with the future work environment.